2022
DOI: 10.1186/s13052-022-01199-5
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and spirometry in this age

Abstract: In the last year, many countries adopted a plan to contain hospital infections by Sars-Cov-2 also limiting pulmonary function tests (PFTs), exclusively to indispensable cases. All the recommendations of the major scientific societies regarding the use of PFTs, in particular spirometry, in the Covid era were formulated in the initial period of the pandemic. Currently, the new scientific knowledge about Sars-Cov-2 and the vaccination among healthcare workers, shown new insight to start doing PFTs again to help t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…This is to a study by the COVID-UPO Clinical Team and Sainaghi in Italy, which found a significantly lower P/F ratio in non-survivor patients compared to survivors (246 [184-300] vs 126 [100-202], p< 0.001). [35] From the statistical analysis in this study, it was found that patients who experienced a decrease in the ratio of PaO2/FiO2 increased the risk of mortality by 43.1 times (95% CI 19.461-95.478; p <0.001). This is consistent with a study by Izcovich A, et al of 1887 patients showing an increase in mortality of 20.3% in patients with a low PaO2/FiO2 ratio (odd ratio 21.17, 95% CI 4.9-91.3).…”
Section: Discussionmentioning
confidence: 65%
“…This is to a study by the COVID-UPO Clinical Team and Sainaghi in Italy, which found a significantly lower P/F ratio in non-survivor patients compared to survivors (246 [184-300] vs 126 [100-202], p< 0.001). [35] From the statistical analysis in this study, it was found that patients who experienced a decrease in the ratio of PaO2/FiO2 increased the risk of mortality by 43.1 times (95% CI 19.461-95.478; p <0.001). This is consistent with a study by Izcovich A, et al of 1887 patients showing an increase in mortality of 20.3% in patients with a low PaO2/FiO2 ratio (odd ratio 21.17, 95% CI 4.9-91.3).…”
Section: Discussionmentioning
confidence: 65%
“…The vaccination availability together with the application of safety protocols gives the opportunity not only to prevent infection spread but also to schedule clinical controls as well as diagnostic procedures which may have been postponed in non-urgent cases, such as pulmonary function tests [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies show that allergy and asthma, if under control, did not represent risk factors for the susceptibility to SARS-CoV-2 [43] , [44] , [45] , [46] . The role of spirometry, in the COVID era, still remains fundamental in the diagnosis and follow-up of respiratory diseases, in compliance with current containment measures [47] .…”
Section: Does Vitamin D Deficiency Increase the Risk And Severity Of ...mentioning
confidence: 99%